2021
DOI: 10.1364/ao.418603
|View full text |Cite
|
Sign up to set email alerts
|

Controlled carrier mean free path for the enhanced efficiency of III-nitride deep-ultraviolet light-emitting diodes

Abstract: Electron overflow from the active region confines the AlGaN deep-ultraviolet (UV) light-emitting diode (LED) performance. This paper proposes a novel approach to mitigate the electron leakage problem in AlGaN deep-UV LEDs using concave quantum barrier (QB) structures. The proposed QBs suppress the electron leakage by significantly reducing the electron mean free path that improves the electron capturing capability in the active region. Overall, such an engineered structure al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This would improve the electron blocking capability in the active region and reduce the electron leakage into the p-region [4]. Moreover, the presence of concave QBs in LED 2 would slow down the hot electrons by lowering the electron MFP before entering into quantum wells in the active region which would play an additional role in reducing the electron leakage [19].…”
Section: Resultsmentioning
confidence: 99%
“…This would improve the electron blocking capability in the active region and reduce the electron leakage into the p-region [4]. Moreover, the presence of concave QBs in LED 2 would slow down the hot electrons by lowering the electron MFP before entering into quantum wells in the active region which would play an additional role in reducing the electron leakage [19].…”
Section: Resultsmentioning
confidence: 99%
“…Through X-ray analysis, it showed no-peak the XRD pattern, indicating the remained bulk structure of the LAO lattice when integrating the ion dopant Dy 3+ . The event that ion Dy 3+ replaced the La 3+ site of the host could be attributed to their same charge by their ionic-radius percentage difference (Dir), as expressed [21],…”
Section: Wled Simulationmentioning
confidence: 99%
“…Computing the activation energy of crystallization yields the reaction mechanism. SSON:Eu phosphors have earlier been examined, however just the luminescence and configuration characteristics were described [6], [7]. Research by Durmus and Davis [8] found that the heat quenching temperature of SSON:Eu is around 600 K. (327 °C).…”
Section: Introductionmentioning
confidence: 99%